2004
DOI: 10.1111/j.1348-0421.2004.tb03472.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Identification of Endothelial Antigens Predominantly Recognized in Kawasaki Disease Patients by Recombinant Expression Cloning

Abstract: We showed IgG immune response against endothelial antigens in sera obtained from convalescent Kawasaki disease (KD) patients after recovery from the disease during the follow‐up period using serological analysis of recombinant cDNA expression library (SEREX) methodology. We identified 46 antigens represented by 69 clones by immunoscreening of a cDNA expression library from tumor necrosis factor‐α (TNFα) treated human umbilical vein endothelial cells (HUVEC) with sera from 4 KD patients. They included ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…The authors used a proteomic approach and human dermal microvascular EC as protein source [20]. Recently, another approach based on serological analysis of recombinant cDNA expression library has been developed to identify target antigens in Kawasaki disease [21].…”
Section: Detection Of Anti-ec Autoantibodies and Identification Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used a proteomic approach and human dermal microvascular EC as protein source [20]. Recently, another approach based on serological analysis of recombinant cDNA expression library has been developed to identify target antigens in Kawasaki disease [21].…”
Section: Detection Of Anti-ec Autoantibodies and Identification Of Thmentioning
confidence: 99%
“…AECA have also been detected in Kawasaki disease [27][28][29]. Using serological analysis of recombinant cDNA expression library, Kaneko et al identified tropomyosin and T-plastin, a cytoskeletal protein, as preferential target antigens for AECA from patients with Kawasaki disease [21].…”
Section: Aeca In Systemic Vasculitidesmentioning
confidence: 99%
“…Recognition of autoantigens by antiendothelial cell antibodies has been reported [8,9]. We previously demonstrated a marked elevation of a B-cell-activating factor belonging to the TNF family (BAFF) [10] before intravenous immunoglobulin therapy (IVIG), and its steep drop after the therapy [11], which suggest that B-cell activation in the acute phase might be involved in the pathogenesis of KD.…”
Section: Introductionmentioning
confidence: 99%
“…Kaneko et al [63] successfully applied serological analyses to a recombinant cDNA expression library in KD patients and identified some EC antigens as targets of AECA, including tropomyosin and T-plastin.…”
Section: Expert Opinionmentioning
confidence: 98%
“…To date, considerable efforts have been made for the identification of AECA autoantigens. As shown in [63] and DNA topoisomerase I [64].…”
Section: Induction Of Coagulationmentioning
confidence: 99%